Shape-controlled Mn–Fe PBA derived micromotors for organic pollutant removal. (14th April 2022) - Huang, Jing; Shan, Qi; Fang, Yanan; Zhao, Ning; Feng, Xiaomiao
Abstract : A new strategy is employed to prepare Mn–Fe PBA derived oxide micromotors with excellent motion performances through co-precipitation and heat treatment, which can be used for organic pollutant degradation with recycling and reusing advantages. Abstract : A new simple strategy to prepare Mn–Fe Prussian blue analogue (PBA) derived oxide micromotors through co-precipitation and heat treatment is demonstrated. The morphology of the precursors could be precisely controlled from cubic-like to spherical-like by introducing citrate. Because of the synergistic catalytic reaction of bimetallic Mn–Fe oxides, micromotors with different shapes could be powered efficiently in H2 O2 solution. In particular, the obtained cubic Mn–Fe oxide micromotors showed strong propulsion at a speed of 71.21 μm s −1 in 1% H2 O2 solution. With dual mechanisms of adsorption bubble separation (ABS) and Fenton oxidation, the cubic Mn–Fe oxide micromotors showed extraordinary removal ability for Rhodamine B (RhB) as a simulated pollutant and could remove up to 95.2% of RhB within 30 minutes. Magnetic Fe3 O4 contained in the component not only could degrade organic pollutants, but also could be recycled by magnetic field and reused with high degradation efficiency. These dual-functional metal oxide catalytic micromotors provide a practical and environmentally friendly strategy for environmental restoration.